Perceptions and practices of fundamental movement skills in grassroots soccer coaches. Issue 4 (August 2022) - Duncan, Michael J.; Weldon, Anthony; Barnett, Lisa M.; Lander, Natalie
This study presents the perceptions and practices of fundamental movement skills (FMS) in grassroots soccer coaches. One hundred and twenty-eight coaches (123 males, 5 females) completed an online mixed-method survey comprising 32 questions relating to: participant demographics, education, and qualifications; FMS perceptions, practices, and assessments, and the importance of FMS constructs; and other factors related to FMS. Frequency analysis was used to assess and report responses to fixed response and Likert-scale questions, and thematic analysis used for open-ended questions. Results indicated that grassroots soccer coaches have an awareness of the concept of FMS and value FMS as a contributor to developing general movement and soccer specific skills. However, there was a tendency for the coaches to conflate FMS with fitness. Coaches in the current study reported that developing FMS was useful to improve soccer development. The coaches suggested they assessed FMS but the measures they employed predominantly focused on more general movement outcomes. No coach used a valid or reliable process-oriented FMS assessment. Coaches used resources to inform their practice for FMS development, but the quality of resources accessed lacked an evidence base, with a reliance on social media. While the coaches in the current study reported valuing FMS, there are gaps in coach education and available evidence-based resources which inhibit the effective development of FMS within grassroots soccer practice. Providing training, qualifications and additional support for coaches related to FMS will aid implementation in practice.